The Implementation of Muzara’ah Aqad in Sapaduoan Sawah System a Case Study in Agam Regency - Sarah Afifah; M. Khairul Arwani; Fahrul Fajar; Muhammad Alwi (Yayasan Lembaga Studi Makwa, 2024)
Agriculture plays a pivotal role in the human economy, serving as one of the most vital and productive sectors. Despite its significance, many agricultural practices continue to adhere to local customs and traditions, often neglecting the principles outlined in sharia mu'amalah, the Islamic commercial jurisprudence that governs economic activities, including agriculture. The core issue lies in the structure and execution of the Sapaduoan Sawah contract, which, while superficially resembling muzara'ah, diverges in several critical aspects. These discrepancies include the terms of the contract, the process of implementation, and alterations made during the contract period, all of which contribute to the invalidation of the Sapaduoan Sawah agreement under sharia law. The research conducted in Koto Baru-Koto Tuo Village, employing a qualitative field study approach, aims to analyze these deviations and explore the possibility of aligning the Sapaduoan Sawah system with the principles of the muzara'ah contract. The findings indicate that the current practices within the Sapaduoan Sawah system not only fail to meet the requirements of muzara'ah but also involve contractual changes that further compromise the integrity of the agreement. These alterations, often made without mutual consent or proper consideration of Islamic legal principles, result in a damaged and voided contract, highlighting the need for reform and education within the community to ensure that agricultural practices align with the ethical and legal standards of sharia mu'amalah. This research underscores the importance of integrating traditional agricultural systems with Islamic jurisprudence to promote fairness, transparency, and justice in economic transactions.